Organ Doses From Diagnostic Medical Radiography—Trends Over Eight Decades (1930 to 2010). Issue 3 (September 2016) - Melo, Dunstana R.; Miller, Donald L.; Chang, Lienard; Moroz, Brian; Linet, Martha S.; Simon, Steven L.
Abstract : Abstract: This study provides a retrospective assessment of doses to 13 organs for the most common radiographic examinations conducted between the 1930s and 2010, taking into account typical technical parameters used for radiography during those years. This study is intended to be a resource on changes in medical diagnostic radiation exposure over time with a specific purpose of supporting retrospective epidemiological studies of radiation health risks. The authors derived organ doses to the brain, esophagus, thyroid, red bone marrow, lungs, breast, heart, stomach, liver, colon, urinary bladder, ovaries, and testes based on 14 common radiographic procedures and compared, when possible, with doses reported in the literature. These dose estimates were based on radiographic exposure parameters described in textbooks widely used by radiologic technologists in training from 1939 to 2010. The derived estimated doses presented here are believed to be representative of typical organs for an average-size adult who might be considered to be similar to the reference person. There were large variations in organ doses noted among the different types of radiographic examinations. Doses were highest in organs within the area imaged and next highest in organs in close proximity to the area imaged. Estimated organ doses have declined substantially [overall 22‐fold (±38)] over time as a consequence of changes in technology, imaging protocols and protective measures. For some examinations, only slight differences were observed in doses for the decades of the 1960s, 1970s, and 1980s due to minor changes in technical parameters. Substantial dose reductions were observed in the 1990s and 2000s. Abstract : Supplemental digital content is available in the text.